Tourism and third sector organizations: synergies for responsible tourism development? - Paula Guerreiro Martins; Ana Maria Alves Ferreira; Carlos Manuel Costa (Tourism & Management Studies)
The main aim of this paper is the analysis of the third sector arts, culture and local development organizations (TSO) participation in the context of tourism planning and development and to understand the characteristics of its connections to the tourism sector in the region of the Algarve, Portugal, a mature sun and sea destination.